Nightwatching eaudiobook A novel. - Sierra, Tracy (Books on Tape, 2024)
Unputdownable · Psychological Suspense · Horror · Tense · Gripping A FALLON BOOK CLUB PICK “Pulse-pounding locked-room suspense.” —Elle “ Nightwatching is like nothing I've read before. I wolfed it down in two sittings; it's amazing.”—Lisa Jewell A footstep on the stairs. A second to react. What happens next will determine everything. Home alone with her young children during a blizzard, a mother tucks her son back into bed in the middle of the night. She hears a noise—old houses are always making some kind of noise. But this sound is disturbingly familiar: it’s the tread of footsteps, unusually heavy and slow, coming up the stairs. She sees the figure of a man appear down the hallway, shrouded in the shadows. Terrified, she quietly wakes her children and hustles them into the oldest part of the house, a tiny, secret room concealed behind a wall. There they hide as the man searches for them, trying to tempt the children out with promises and scare the mother into surrender. In the suffocating darkness, the mother struggles to remain calm, to plan. Should she search for a weapon or attempt escape? But then she catches another glimpse of him. That face. That voice. And at once she knows her situation is even more dire than she’d feared, because she knows exactly who he is—and what he wants.